Flower Development in Cassava Is Feminized by Cytokinin, While Proliferation Is Stimulated by Anti-Ethylene and Pruning: Transcriptome Responses - Oluwasanya, Deborah; Esan, Olayemisi; Hyde, Peter T.; Kulakow, Peter; Setter, Tim L. (Frontiers in Plant Science, 2021)
Cassava, a tropical storage-root crop, is a major source of food security for millions in the tropics. Cassava breeding, however, is hindered by the poor development of flowers and a low ratio of female flowers to male flowers. To advance understanding of the mechanistic factors regulating cassava flowering, combinations of plant growth regulator and pruning treatments were examined for their effectiveness in improving flower production and fruit set in field conditions. Pruning the fork type branches that arise at the shoot apex immediately below newly formed inflorescences stimulated inflorescence and floral development. The anti-ethylene plant growth regulator silver thiosulfate (STS) also increased flower abundance. Both pruning and STS increased flower numbers while having minimal influence on sex ratios. In contrast, the cytokinin benzyladenine (BA) feminized flowers without increasing flower abundance. Combining pruning and STS treatments led to an additive increase in flower abundance; with the addition of BA, over 80% of flowers were females. This three-way treatment combination of pruning+STS+BA also led to an increase in fruit number. Transcriptomic analysis of gene expression in tissues of the apical region and developing inflorescence revealed that the enhancement of flower development by STS+BA was accompanied by downregulation in of several genes associated with repression of flowering, including homologs of TEMPRANILLO1 (TEM1), GA receptor GID1b, and ABA signaling genes ABI1 and PP2CA. We conclude that flower-enhancing treatments with pruning, STS and BA create widespread changes in the network of hormone signaling and regulatory factors beyond ethylene and cytokinin.